Documentos de descubridores y pobladores del Nuevo Reino de Granada (1520-1551): estado de lengua. - Carrera de la Red, Micaela (Revista de Filología Románica, 2001)
In this article rny aim is to point out sorne phonological changes in the consonantical Spanish system during the first half of ihe 161h century (from 1520 to 1551) analysing texis wrinen in Nuevo Reino de Granada, as colonial Colombia carne to be nanied. Ihe basis of analysis is a paleographic transcription of 38 documents frorn the Archivo General de Indias in Seville. A description of spelling variation is rnainly attempted. Sociolinguistic factors such as Ihe sociocultural level and the dialectal differences of the earliest settlers in the area have been also considered. It is by 1540 when emergence of graphemic features becomes an evidence of phonological change. This change includes the loss distinction of labials, the devoicing and merger of sibilants (seseo) and the devoicing, merger and backing of 1/1 1/, the aspiration of initial /h/ corning ftom Latin 2-, and so on. - Both patrimonial words and indigenisms share graphernic variation and phonological change.